Fragmentation of daily rhythms associates with obesity and cardiorespiratory fitness in adolescents: The HELENA study. Issue 6 (December 2017) - Garaulet, Marta; Martinez-Nicolas, Antonio; Ruiz, Jonatan R.; Konstabel, Kenn; Labayen, Idoia; González-Gross, Marcela; Marcos, Ascensión; Molnar, Dénes; Widhalm, Kurt; Casajús, Jose Antonio; De Henauw, Stefaan; Kafatos, Anthony; et al.
Summary: Background & aims: Chronobiology studies periodic changes in living organisms and it has been proposed as a promising approach to investigate obesity. We analyze the association of the characteristics of the rest-activity rhythms with obesity, cardiorespiratory fitness and metabolic risk in adolescents from nine European countries. Methods: 1044 adolescents (12.5–17.5 y) were studied. Circadian health was evaluated by actigraphy with accelerometers (Actigraph GT1M). Characteristics of the daytime activity such as fragmentation (intradaily variability), estimated acrophase, and 10 h mean daytime activity index were obtained. Body composition was assessed using Bioelectrical-Impedance-Analysis, skinfold thickness, air-displacement-plethysmography and Dual-energy-X-ray-Absorptiometry. Cardiorespiratory fitness (VO2max ) and metabolic risk were studied. Results: Highly fragmented activity rhythms were associated with obesity and central adiposity (P < 0.05). Obese adolescents had ∼3 times higher odds of having a high fragmentation of daytime activity compared to normal weight adolescents OR (95% CI) = 2.8 (1.170, 6.443). A highly fragmented rhythm was also related to lower cardiorespiratory fitness and higher metabolic risk (P < 0.05) so those adolescents classified as low fitness showed a significantly higher fragmentation of daytime activity than those included in the high fitness group (P < 0.0001). Other characteristics of the rhythms such as smaller 10 h daytime mean activity index and delayed estimated acrophase were also related to obesity and metabolic risk (P < 0.05). Conclusions: Our results indicate that the daily organization of the rest-activity cycle is more fragmented in obese and less fit adolescents and correlates with higher metabolic risk. This fact reinforces our hypothesis that disturbances in daily rhythms can be considered as sensitive markers of poorer adolescent's health.